INNOSC Theranostics and Pharmacological Sciences 2020
DOI: 10.36922/itps.v3i2.935
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Curcumin and Folic Acid as Potent Inhibitors of Human Transmembrane Protease Serine 2 in the Treatment of COVID-19

Abstract: Background. Human transmembrane protease 2 (TMPRSS2) protein is essential for priming spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in association with human angiotensin-converting enzyme 2 (ACE2) surface receptor to facilitate viral invasion into host human cell through ACE2 receptor. Impeding TMPRSS2 protein activity is currently a preferred choice of the treatment of coronavirus disease 2019 (COVID-19) which is caused by SARS-CoV-2. Curcumin and folic acid are potential candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…The transmembrane protein serine protease 2 (TMPRSS2) facilitates the entry of SARS-CoV-2 from the spike protein (Hoffmann et al, 2020). In silico analyses focusing on TMPRSS2 showed that curcumin forms four hydrophobic interactions and an H-bond with TMPRSS2 (Motohashi et al, 2020). These findings corroborated results of in vitro studies where curcumin treatment led to the downregulation of TMPRSS2 in prostate cancer cells (Zhang et al, 2007;Thangapazham et al, 2008).…”
Section: In Silico Models Predicting the Antiviral Effects Of Curcumin Against Sars-cov-2supporting
confidence: 65%
“…The transmembrane protein serine protease 2 (TMPRSS2) facilitates the entry of SARS-CoV-2 from the spike protein (Hoffmann et al, 2020). In silico analyses focusing on TMPRSS2 showed that curcumin forms four hydrophobic interactions and an H-bond with TMPRSS2 (Motohashi et al, 2020). These findings corroborated results of in vitro studies where curcumin treatment led to the downregulation of TMPRSS2 in prostate cancer cells (Zhang et al, 2007;Thangapazham et al, 2008).…”
Section: In Silico Models Predicting the Antiviral Effects Of Curcumin Against Sars-cov-2supporting
confidence: 65%
“…Based on in silico data, curcumin can interact with SARS-CoV-2 Spike RBD (Shanmugarajan et al, 2020), hACE2 (Subbaiyan et al, 2020), and TMPRSS2 as well (Motohashi et al, 2020). These data align with our results that curcumin inhibited PSV entry and syncytia formation.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analysis showed that curcumin has a high affinity for binding to the spike glycoprotein through the formation of six hydrogen bonds (Maurya et al, 2020), thus, curcumin has the potential to prevent the binding of the viral spike protein to the ACE2 receptor and inhibit the initiation of the host cell infection process. Moreover, curcumin forms four hydrophobic interactions via hydrogen bonds with TMPRSS2, which may inhibit cellular entry through the cell fusion mechanism (Motohashi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a model of acute lung injury, treatment with curcumin was reported to increase PaO 2 , to decrease pulmonary oedema and to improve lung function ( Cheng et al, 2018 ). At the molecular level, among other antiviral mechanisms ( Rattis et al, 2021 ), curcumin has been reported to show high affinity for both SARS-CoV-2 spike (S) glycoprotein and its cellular receptor, ACE2 and to bind TMPRSS2, suggesting a capacity to block viral attachment to target cells ( Maurya et al, 2020 ; Motohashi et al, 2020 ; Shanmugarajan et al, 2020 ). Curcumin is also thought to interfere with endosomal acidification, an essential step in the SARS-CoV-2 replication cycle ( Vishvakarma et al, 2011 ).…”
Section: Anti-sars-cov-2 Properties Of Curcumin Through Anti-hif-1α F...mentioning
confidence: 99%